Medical air-purifying machine - Chen Jixiong; Yu Aoyuan; Su Jiaji (1994)
The utility model relates to a medical air-purifying machine, which is mainly composed of a shell 1, a primary filter 19 arranged in the shell 1, an activated carbon filter 18, a blower fan 10, an ultraviolet lamp 14 and a high efficiency filter 7. The utility model is characterized in that a degerming chamber is arranged in the shell 1, the ultraviolet lamp 14 is arranged in the degerming chamber, the high efficiency filter 7 is positioned above the ultraviolet lamp 14, the blower fan 10 is positioned below the degerming chamber, and a negative oxygen ion generator is arranged in the shell 1adjacent to an air outlet. The utility model overcomes the defects of large electric power consumption, small wind rate and poor purifying effect in actual use in existing similar products, and provides the air-purifying machine with large wind rate and high degerming effect.